Gambaran Kepatuhan Penulisan Resep Pada Pasien BPJS Poli Spesialis Penyakit Dalam Dengan Formalium Nasional Periode Januari– Februari Tahun 2021 di RSI PKU Muhammadiyah Pekajangan - Puji Ayu Yasta'fifna (Jurnal Adijaya Multidisplin, 2023)
The national formulary is a list of selected drugs which is used as a referencein the services of the Social Security Administering Body to make it easier fordoctors to write prescriptions, but in reality there are still doctors who writeprescriptions that are not in accordance with the national formulary.This study aims to determine the level of compliance with prescriptionwriting in patients with BPJS poly specialist internal medicine with the nationalformulary for the period January - February 2021 at RSI PKU MuhammadiyahPekajangan. This research is a retrospective descriptive study using a sample of 200recipes.The results showed that the conformity of writing prescriptions with thenational formulary for drug items was 87%, while drug items that were not inaccordance with the national formulary were 13%. Keywords : Compliance with prescription writing, Outpatient of BPJS,National Formulary